Gramsci Dictionary - Dizionario gramsciano: Piero Sraffa - Frosini, Fabio (International Gramsci Journal, 2025)
Piero Sraffa, a few years younger than Gramsci, first met him in Turin in 1919. He followed closely the activity of the Ordine Nuovo group and its journal, having a letter of his published anonymously in it, to Gramsci’s critical discussion in reply . The two then met again in Rome when , as parliamentary deputy having immunity, Gramsci had returned to Italy from Moscow and Vienna. Sraffa became a decisive figure for Gramsci after the latter’s arrest, opening an unlimited account for him at a Milanese bookshop and, through Tanja Schucht, became Gramsci’s channel for communication with the Italian Communist Party’s Foreign Centre in France. At a distance and indirectly, then, the two men acted as stimuli for each other, mainly for Gramsci but the reciprocity in the relationship should not be overlooked. In 1932, for example, there were requests for Gramsci to further his work on the intellectuals in Italian history, and on the recent publications of the philosopher-historian-literary figure, Benedetto Croce. Gramsci in his turn asked Sraffa for information, for example, on Machiavelli and economic science, and on David Ricardo and philosophy and the two exchanged opinions, once more through Tanja, on the position of Italian Jews under fascism. Sraffa also chanelled administrative efforts to have a revision of Gramsci’s trial and some attempts at gaining his freedom.